Integration of biosensors based on microfluidic: A review - Yousefi, A.T.; Bagheri, Samira; Kadri, Nahrizul Adib (Emerald, 2015)
Purpose - Biotechnology is closely associated to microfluidics. During the last decade, designs of microfluidic devices such as geometries and scales have been modified and improved according to the applications for better performance. Numerous sensor technologies existing in the industry has potential use for clinical applications. Fabrication techniques of microfluidics initially rooted from the electromechanical systems (EMS) technology. Design/methodology/approach - In this review, we emphasized on the most available manufacture approaches to fabricate microchannels, their applications and the properties which make them unique components in biological studies. Findings - Major fundamental and technological advances demonstrate the enhancing of capabilities and improving the reliability of biosensors based on microfluidic. Several researchers have been reported verity of methods to fabricate different devices based on EMS technology due to the electroconductivity properties and their small size of them. Therefore, controlled fabrication method of MEMS plays an important role to design and fabricate a highly selective detection of medical devices in a variety of biological fluids. Stable, tight and reliable monitoring devices for biological components still remains a massive challenge and several studies focused on MEMS to fabricate simple and easy monitoring devices. Originality/value - This paper is not submitted or under review in any other journal.